Studi Kualitas Hidup Penderita Gagal Ginjal Pada Remaja Yang Menjalani Hemodialisa di RSUD Bahteramas Provinsi Sulawesi Tenggara Tahun 2023 - Nofi Sofiana; Hartati Bahar; Hariati Lestari (Jurnal Anestesi, 2024)
Pre-survey conducted in Southeast Sulawesi Province at the Bahtermas Hospital. A significant risk of decreasing kidney function characterizes kidney failure as a clinical disease that, in certain cases, requires long-term kidney replacement treatment, such as hemodialysis or kidney transplantation. There will be two male and two female victims, ages 15 to 24, in 2023. There will be two female and eight male patients between the ages of 15 and 24 in 2022. There will be two female and three male victims between the ages of 15 and 24 in 2021. The descriptive qualitative research method is a standard study approach that involves five respondents, two regular informants (the head of the hemodialysis lab and staff in the hemodialysis room) and four key informants (adolescents suffering from kidney failure). Data are collected through interviews, observations, and documentation. The study's findings demonstrate that, although stress and depression were previously experienced by the patients, these issues can be effectively resolved with behavioral adjustments and hope among teenagers receiving hemodialysis at Bahteramas Hospital in Southeast Sulawesi Province in 2023. recuperated from the individuals. In addition, it is impacted by the living environment, health services, friends' support, and social support